Geotour guide competency in the context of safety management - Rhama, Bhayu; Reindrawati, Dian Yulie (Opción, 2019)
This study wanted to determine the level of geotour guide competency in the context of safety management in Batur Geopark, Bali, Indonesia via a purposive method through interviews. The researcher collected the data by interviewing 1 person from a travel agency, 1 headman, 2 tour guides and 2 people from the tourism agency. The result shows that several institutions focus on emergency situations, such as search and rescue institutions. In conclusion, the geotour guide standards of competency in Batur Geopark need to be created because of the different capabilities involved.